MOTIVASI ORANG TUA DALAM MEMILIH SEKOLAH FULL DAY DI SD IT TEUKU UMAR - Dian Azhara Putri; Azhari, Muhammad (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2023)
This research is motivated by one of the most important things in determining education is the role of parents towards children. Of course parents have certain reasons for placing their children in the school of choice in accordance with the vision and mission and also looking at the school's program perspective. This research aims to determine parents' motivation in choosing a full day school at SD IT Teuku Umar and to determine the supporting factors and inhibiting factors for parents in choosing a full day school at SD IT Teuku Umar. This type of research is field research using a qualitative approach. Data collection techniques are observation, interviews and documentation. Meanwhile, the technical data analysis used in this research is qualitative data analysis consisting of data reduction, data presentation and drawing conclusions. The results of the research show that one of the motivations for parents in choosing a full day school at SD IT Teuku Umar is that parents want their child to become a hafidz of the Qur'an, be a pious child, have akhlakul kharimah traits and receive character development. The supporting factors that parents feel in choosing a full day school at SD IT Teuku Umar are that the school has competent teachers, there is good cooperation between parents and teachers and the school programs offered. Meanwhile, the inhibiting factors for parents in choosing a full day school at SD IT Teuku Umar are paying tuition fees and forgetting to deliver supplies when they are busy working.